A SnO2 nanoparticle/nanobelt and Si heterojunction light-emitting diode - Chen, Rui (2011)
Single-crystalline zero-dimensional tin dioxide (SnO2) nanoparticles and one-dimensional SnO2 nanobelts were synthesized on silicon (Si) substrates with different seed layer coatings by simple vapor-phase transport method. The crystal structure and morphology of the as-synthesized products were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, and Raman scattering spectroscopy. Both geometrically different nanostructures were further employed to fabricate the light-emitting diodes and showed dominant red and green emission bands at room temperature, which were ascribed to the deep defect states in SnO2. However, SnO2-nanobelts-based light-emitting diodes showed another violet emission peaking at ca. 400 nm which was attributed to the shallow defect state related to the surface states/defects. The different emission performance between nanoparticle and nanobelts devices was attributed to the larger surface-to-volume ratio of the nanobelts, which was confirmed by the Raman and photoluminescence analysis. A thin SiO2 intermediate layer was found to be crucial in achieving light emission from a n-SnO2/p-Si heterojunction with large valence band offset (ca. 2.96 eV), by which sufficient potential-energy difference can be maintained between SnO2 and Si, thus facilitating the tunneling injection of holes.